Asthmna control and prior medical care of patients presenting with acute asthma at the emergency department - Lee, P.Y.; Khoo, E.M. (2003)
Seventy patients presented with acute asthma at the emergency department of the University of Malaya Medical Centre, Kuala Lumpur were recruited over a two-week period in July 2001. Fifty-one (73) patients belonged to the poorly controlled group. Fifty-seven (81) patients were using inhaled salbutamol but 21 (30) were still using oral short acting salbutamol. Only 32 (46) patients used inhaled corticosteroids. In the poorly controlled group, 22 (43.1) patients were not on regular inhaled corticosteroids, 35 (68.6) were not receiving "add-on" medication and 18 (35) did not have regular follow up. The emergency department should implement a protocol for asthma management and follow up to achieve better long term patient care.